2021
DOI: 10.9734/jamb/2021/v21i230325
|View full text |Cite
|
Sign up to set email alerts
|

Biological Properties and Phytochemical Analysis of Fractions and Total Extracts of Cylicodiscus gabunensis Harms and Morinda lucida Benth

Abstract: Two plants used in traditional medicine from Gabon were studied. The aim of this study was to study the biological properties and phytochemical analysis of Cylicodiscus gabunensis Harms and Morinda lucida Benth. These extracts were subjected to antimicrobial (diffusion, dilution), antioxidant (DPPH, ABTS) and inhibition of protein denaturation. The water-ethanol, water-acetone extracts and the partitioned extracts (F1 and F2) of Cylicodiscus gabunensis showed the greatest antibacterial activity on the majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…This suggests that the active principles in the extracts may be from the groups of compounds mentioned above. This is in conformity with previous phytochemical studies, which revealed the presence of these secondary metabolites to be responsible for the medicinal properties of these plants [ 16 , 33 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This suggests that the active principles in the extracts may be from the groups of compounds mentioned above. This is in conformity with previous phytochemical studies, which revealed the presence of these secondary metabolites to be responsible for the medicinal properties of these plants [ 16 , 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…Tis suggests that the active principles in the extracts may be from the groups of compounds mentioned above. Tis is in conformity with previous phytochemical studies, which revealed the presence of these secondary metabolites to be responsible for the medicinal properties of these plants [16,33]. Te isolation of pure compounds from these plant extracts is recommended to determine their full active potential and ascertain the actual phytochemicals responsible for the anti-onchocerca activity of the plant extracts.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This practice, which consists in exploiting the knowledge accumulated over the centuries, uses plants whose flora abounds in an important reserve of aromatic and medicinal character for traditional use. Carapa procera, Chenopodium ambrosioides, Mammea africana and Maranthes gabunensis represent some of the plants frequently used by the populations of Haut-Ogooué for their antibacterial, antihypertensive, analgesic, febrifuge, anti-inflammatory, antimalarial, anthelmintic, insecticide and insect repellent properties [3,4]. For the moment, chemical and biological investigations remain to be carried out in order to develop them and be able to better exploit their properties.…”
Section: Introductionmentioning
confidence: 99%